Case report: prehospital use of intranasal ketamine for paediatric burn injury. Issue 4 (3rd February 2011) - Reid, C; Hatton, R; Middleton, P
Abstract : In this study, the administration of an intravenous ketamine formulation to the nasal mucosa of a paediatric burn victim is described in the prehospital environment. Effective analgesia was achieved without the need for vascular or osseous access. Intranasal ketamine has been previously described for chronic pain and anaesthetic premedication. This case highlights its potential as an option for prehospital analgesia.